Large-Eddy Simulation of air-fuel mixing in Dry Low NOx GTU Combustor - Aguado, Pablo (Cranfield University, 2014)
The in-house code FLAMENCO is developed to simulate the mixing process in a Dry Low NOx GTU Combustor. The physical approach is defined to model 3D-unsteady, compressible, multi-species flows where turbulence plays a major role. For this purpose, Large Eddy-Simulation is applied in conjunction with high-order schemes and stable formulation of volume fraction advection. Regarding the numerical structure, FLAMENCO is a Finite-Volume Godunov-type algorithm equipped with 5th and 2nd Order non-oscillatory reconstruction in space and 2nd Order, 4-Stages Explicit Runge-Kutta scheme for integration in time. From a mathematical point of view, the multi-species approach is governed by the 5-Equation Transport Model and is thermodynamically defined by iso-baric and perfect gas considerations, which prevent pressure oscillations. Finally, an HLLC approximate Riemann solver computes convective fluxes and 2nd Order centred differences accounts for dissipation terms. Previous research with an old version of FLAMENCO failed due to low dissipation in the jet injector tube. This issue stems from local energy being uncontrollably introduced in this small region, leading to unphysical pressure values. It was found that the combination of reflecting inflow, small cells and high gradients is responsible for acoustic wave reflection and amplification. To overcome this problem, a number of modifications including boundary conditions (Partially Non-reflecting, Non-reflecting and Nozzle-type subsonic inflows and outflows), an Adaptive Reconstruction Scheme, a more dissipative reconstruction scheme (5th Order WENO) and grid changes (only in jet injector) have been introduced. As a result, local energy generation and evacuation become balanced within physical boundaries, providing stable conditions in the whole domain. Initially, extensive validation of the new numerical approach is conducted through contrasted test cases such as Stationary and Moving Contact Wave, Shock Tube Problem, Kelvin-Helmholtz Instability and 2D-3D Explosion Problems. In the same way, strategies intended to overcome the low dissipation problem are analysed in a representative configuration. After the validation process, several simulations involving coarse and fine grids and different reconstruction schemes are run in the Dry Low NOx GTU Combustor. Finally, results are compared with experimental data, showing really good accuracy for 5th Order schemes, which is specially surprising in the coarse grid. In this way, highly turbulent, heterogeneous structures such as Vortex Breakdown, Central Recirculation Zone, Precessing Vortex Core and Secondary Vortices are very well captured, demonstrating the suitability of the mixing model to deal with highly turbulent flows where critical shear layers and high mixing ratios coexist in confined domains.